ANALYSIS OF THE IMPLEMENTATION OF GREEN TRANSPORTATION TO REALIZE A GREEN AND SUSTAINABLE CITY (STUDY ON THE RAPID TRANSIT BUS TRANSPORTATION MODE IN MEDAN CITY) - Annisa Aulia Lubis; Muhammad Imanuddin Kandias Saraan (OPINI: Journal of Communication and Social Science, 2025)
Rising motor vehicle ownership in Medan City has intensified traffic congestion and carbon emissions, worsening urban air pollution. Data from the Medan Environmental Agency show that transportation-sector carbon emissions increased from 1,575 tons in 2020 to 2,154 tons in 2022. Kumparan Tech (2019) also reported an Air Quality Index (AQI) score of 78 for Medan, placing it among Indonesia’s five most polluted cities. In response, the Medan City Government introduced an electric-based Bus Rapid Transit (BRT) system as a green transportation initiative aligned with sustainable development goals. Nevertheless, its implementation remains suboptimal due to inadequate bus stop facilities, limited fleet availability, insufficient supporting infrastructure, declining ridership linked to the digital payment system, and weak stakeholder coordination. This descriptive qualitative study collected data through interviews, observation, and documentation, guided by Litman’s (2015) green transportation indicators: safety, environmental impact, comfort, and land use. Findings highlight unmet standards, limited public outreach, and incomplete inter-stakeholder collaboration, prompting recommendations for stronger regulation, improved coordination, and better service quality.